2019
DOI: 10.1007/s10725-019-00476-4
|View full text |Cite
|
Sign up to set email alerts
|

OsMND1 regulates early meiosis and improves the seed set rate in polyploid rice

Abstract: The meiotic processes of most polyploid rice (Oryza sativa) are genetically abnormal, leading to low pollen fertility, which results in low seed set rates. Some polyploid meiosis stability (PMeS) lines with high seed set rates have been bred but their meiotic mechanisms remain unknown. In this study, we investigated the function of OsMND1 regulated polyploid rice meiosis. OsMND1 localized in the nucleus, and its expression level in panicles of PMeS line HN2026-4x was higher than in HN2026-2x and the other line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…These two lines display regular meiotic behavior, with bivalents and quadrivalents. The existence of genetic chromosome pairing PMeS control was confirmed by the persistent meiotic stability of the two lines even after several generations (Xiong et al, 2019).…”
Section: Control Of Chromosome Pairing In Polyploid Grassesmentioning
confidence: 85%
“…These two lines display regular meiotic behavior, with bivalents and quadrivalents. The existence of genetic chromosome pairing PMeS control was confirmed by the persistent meiotic stability of the two lines even after several generations (Xiong et al, 2019).…”
Section: Control Of Chromosome Pairing In Polyploid Grassesmentioning
confidence: 85%
“…In addition, loss function of MOF1a also increased the frequency of PMCs with abnormal chromosome behaviors in seven stage of meiosis, and the most common abnormality was the straggle chromosome. In a previous study, many mutants of meiosis-related genes, such as ZIP4 , OsREC8 , MRE11 , OsSGO1 , HEI10 , OsDMC1 , and OsMND1, caused similar straggle chromosomes during meiosis process because of abnormal homologous synapsis or double strand break [ 65 , 66 , 67 , 68 , 69 , 70 , 71 ]. Disorder of microtube distribution is also considered a key reason of chromosome behaviors [ 9 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that stable meiosis, timely tapetum degradation, and normal mitochondrial development were the critical factors ensuring the high pollen fertility of PMeS lines (He et al, 2010). Recently, Xiong et al (2019) revealed that the rice homolog of the gene MND1, which plays a role in meiosis in yeast and Arabidopsis, also plays a crucial role in improving the seed set rate in PMeS lines. They showed that the OsMND1 expression level in panicles of a PMeS line was higher than in the diploid lines or in the other autotetraploid line with low seed set rate and OsMND1 overexpression improved pollen fertility and seed set.…”
Section: Pmes (Polyploid Meiosis Stability) and Neo-tetraploidy: Emermentioning
confidence: 93%
“…They showed that the OsMND1 expression level in panicles of a PMeS line was higher than in the diploid lines or in the other autotetraploid line with low seed set rate and OsMND1 overexpression improved pollen fertility and seed set. The meiotic behavioral observations suggested that the effects of OsMND1 might be maintaining the balance of synapsis and recombination (Xiong et al, 2019). However, it is still unknown why the expression level of OsMND1 was lower in autotetraploid line with low seed set rate than the PMeS line.…”
Section: Pmes (Polyploid Meiosis Stability) and Neo-tetraploidy: Emermentioning
confidence: 99%
See 1 more Smart Citation